Stage-structured plastisphere succession sustains antibiotic resistomes on microplastics during full-scale A2/O wastewater treatment - Xin Hou; Xiaoran Li; Yunan Lin; Xiaoyan Li; Wen Li; Lei Zhang; Jiamin Li; Ziming Jiang; Sen Wang; Xiaotong Wang; Xianhua Liu (Water Research, 2027)

Physics-environment augmented Attention-LSTM approach for mooring tension prediction - Jin Hu; Dongsheng Qiao; Pengfei Liu; Guoguang Sun; Ziming Wang; Guoqiang Tang; Yunfei Teng; Lin Lu; Jinping Ou (Ocean Engineering, 2026)

Heavy metal leaching risks of MSWI fly ash from industrial solid waste co-incineration: Full-scale metal-specific screening and management implications - Lifang Gong; Ziming Lin; Lu Dong; Hongyun Hu; Yongda Huang; Huiming Liu; Guangzhao Guo; Xiaodong Zeng; Hong Yao (Process Safety and Environmental Protection, 2026)

Perovskite-based flexible films for high-energy radiation shielding and detection - Jinlong Bai; Weiqiang Gong; Yi Zhao; Zizheng Li; Yi Chang; Ziming Wang; Tingting Liu; Xinci Zhang; Xitian Zhang; Feng Gao; Lin Li (Chemical Engineering Journal, 2026)

TDCIPP induces placental dysfunction and fetal growth restriction via oxidative stress-mediated PINK1/Parkin mitophagy - Ziming Lin; Mingqi Hu; Ruijie Li; Xiaorui Gong; Man Zhao; Haiyan Zhang; Jin Xuan; Wenlan Qiao; Anna Li (Food and Chemical Toxicology, 2026)

Effects and Correlations of Acetic Acid Concentration on the Combustion Characteristics and Functional Groups of Coal - Junhong Si; Ziming Fan; Lin Li; Yiqiao Wang; Zihao Zhao (Natural Resources Research, 2026)

Molecular and optical signatures of labile dissolved organic matter during bloom senescence in the Amundsen Sea Polynya - Hui Lin; Qiang Hao; Wei Zhang; Zhenwei Yan; Hao Zhang; Ziming Fang; Yuan Gao; Yong Yu; Ding He (Limnology and Oceanography, 2026)
The Amundsen Sea Polynya (ASP) in the Southern Ocean serves as a potentially significant carbon sink, where phytoplankton blooms drive intense primary production and dissolved organic matter (DOM) cycling. This study focuses on DOM dynamics during the late‐summer bloom phase dominated by Phaeocystis antarctica . Despite the ASP's high productivity, DOM characteristics and their response to bloom senescence remain poorly resolved, limiting insights into carbon sequestration efficiency. We integrated absorbance and fluorescence spectroscopy with Fourier transform ion cyclotron resonance mass spectrometry to analyze seawater samples collected along transects in the ASP during austral summer 2022. Key findings include non‐exponential chromophoric DOM spectra with distinct shoulders at 270–290 nm (aromatic amino acids) and 300–350 nm (mycosporine‐like amino acids), elevated protein‐like fluorescent DOM components linked to P. antarctica degradation, and enrichment of labile, low‐molecular‐weight compounds ( −1 ) amid reduced chlorophyll a (3.81 ± 0.77 mg·m −3 ), indicating DOM release under iron‐replete, nitrate‐limited conditions. This work advances knowledge by identifying unique phytoplankton‐derived DOM signatures that challenge conventional optical metrics like spectral slopes in polar systems, highlighting autochthonous production over terrestrial inputs. Broader implications include improved predictions of carbon cycling in expanding polynyas under climate change, emphasizing reduced sequestration due to labile DOM remineralization and its vulnerability to warming‐induced shifts in Antarctic ecosystems.

Optimisation study of a geometric-VOF model based on elementary symmetric polynomial and adaptive time-step Crank-Nicolson method - Ziming Xu; Yanjun Liu; Zaibin Lin; Shuting Huang; Hao Chen; Gang Xue (Ocean Engineering, 2026)

Mechanisms of saprolite karstification driving subsurface karst expansion in the Dacun Tunnel, Yunnan, China - Chenxi Wang; Jipu Chen; Lin Tian; Bin Li; Ziming Ye (Carbonates and Evaporites, 2026)

Effect of hydrogen blending ratio on the air entrainment and lift-off characteristics of inclined methane jet flames - Ziming Lin; Kun Zhao; Huikun Wang; Zhenhua Tang; Situo Li (Fuel, 2026)

Highly reliable deep eutectic gel electrolyte with synergistic conductivity, fatigue resistance, and freezing tolerance for high-performance flexible supercapacitors - Changjian Zhou; Ziming Zhu; Jie Li; Xiangyu Lin; Xujuan Huang; Xu Xu; He Liu (Chemical Engineering Journal, 2026)

Bright and stable green-emitting quantum dots with universal surface modifiability for diagnostic probes - Ning Li; Dexia Zhou; Ya Liu; Ziming Zhou; Zhaobing Tang; Siqi Jia; Ruili Wu; Huaibin Shen; Yanbing Lv; Lin Song Li (Chemical Engineering Journal, 2026)

The Observed and Projected Changes of Global Monsoons: Current Status and Future Perspectives - Tianjun Zhou; Xiaolong Chen; Wenxia Zhang; Bo Wu; Ziming Chen; Jie Jiang; Xin Huang; Shuai Hu; Meng Zuo; Wenmin Man; Lixia Zhang; Zhun Guo; et al. (Advances in Atmospheric Sciences, 2026)
The global monsoon system, encompassing the Asian-Australian, African, and American monsoons, sustains two-thirds of the world’s population by regulating water resources and agriculture. Monsoon anomalies pose severe risks, including floods and droughts. Recent research associated with the implementation of the Global Monsoons Model Intercomparison Project under the umbrella of CMIP6 has advanced our understanding of its historical variability and driving mechanisms. Observational data reveal a 20th-century shift: increased rainfall pre-1950s, followed by aridification and partial recovery post-1980s, driven by both internal variability (e.g., Atlantic Multidecadal Oscillation) and external forcings (greenhouse gases, aerosols), while ENSO drives interannual variability through ocean-atmosphere interactions. Future projections under greenhouse forcing suggest long-term monsoon intensification, though regional disparities and model uncertainties persist. Models indicate robust trends but struggle to quantify extremes, where thermodynamic effects (warming-induced moisture rise) uniformly boost heavy rainfall, while dynamical shifts (circulation changes) create spatial heterogeneity. Volcanic eruptions and proposed solar radiation modification (SRM) further complicate predictions: tropical eruptions suppress monsoons, whereas high-latitude events alter cross-equatorial flows, highlighting unresolved feedbacks. The emergent constraint approach is booming in terms of correcting future projections and reducing uncertainty with respect to the global monsoons. Critical challenges remain. Model biases and sparse 20th-century observational data hinder accurate attribution. The interplay between natural variability and anthropogenic forcings, along with nonlinear extreme precipitation risks under warming, demands deeper mechanistic insights. Additionally, SRM’s regional impacts and hemispheric monsoon interactions require systematic evaluation. Addressing these gaps necessitates enhanced observational networks, refined climate models, and interdisciplinary efforts to disentangle multiscale drivers, ultimately improving resilience strategies for monsoon-dependent regions.

Desorption dynamics of black carbon in a subtropical estuary - Qinghua Zhang; Weifeng Yang; Ziming Fang; Zeheng Lin; Minfang Zheng; Mengya Chen (Marine Chemistry, 2025)

Application of nanomaterials in central nervous system disorders - Yixuan Deng; Yani Feng; Bangming Ye; Lei Hu; Lixin Qi; Chenyi Wang; Chunting Zhou; Guanhao Liu; Xiuying Gao; Congying Lin; Qiang Ding; Ziming Zhao; et al. (Psychopharmacology, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Composite antimicrobial films activated by essential oil pickering emulsions: Preparation, characterization and application in pork preservation - Lin Liu; Tanghui Liu; Guihong Li; Qingqing Tan; Anjun Tang; TingTing Wen; Ziming Li; Hai Chi; Hongrui Chen; Jie Tang; Xingzhong Zhang (Food Bioscience, 2025)

Axial compressive behavior and deterioration pattern of stainless-clad bimetallic square steel tubes under chloride ion environment - Dong Li; Mingxuan Lin; Ziming Wang; Yuan Sang; He Zhao; Xiaoqiang Yang (Engineering Structures, 2025)

A zwitterionic polymer binder Integrating multiple dynamic interactions enables High-Performance Lithium − Sulfur batteries - Xiangyu Lin; Yong Wen; Danna Ma; Jie Li; Ziming Zhu; Shanshan Wang; He Liu; Xu Xu; Xujuan Huang (Chemical Engineering Journal, 2025)

Covalent and non-covalent cross-linked based polymer binders for high-sulfur-loading lithium-sulfur batteries - Danna Ma; Yong Wen; Xiangyu Lin; Jie Li; Ziming Zhu; Shanshan Wang; He Liu; Xu Xu (Chemical Engineering Journal, 2025)

Restorative effects of highway roadside urban forests: A simulated approach - Qunyue Liu; Kunneng Jiang; Ziming Wang; Yumeng Wang; Huiting Zhang; Qingju Wang; Hangqing Chen; Donghuang Lin; Ulrika K. Stigsdotter; Yuxiang Lan (Forest Policy and Economics, 2025)

Design of impact ultrasonic penetrator and optimization of impact efficiency - Yinchao Wang; Ziming Yu; Zihao Yin; Weiwei Zhang; Lin Zu; Guanghong Tao; Suyang Yu (Advances in Space Research, 2025)

Etching and isolation technique for synthesis of CNTs-encapsulated NiSe2/CoSe2 for supercapacitor applications - Jiangshan Gao; Yide Hao; Shuyan Lin; Ziming Zhang; Huifang Li; Yan He (Chemical Engineering Journal, 2025)

Concurrent Inter‐Model Spread of Boreal Winter Westerly Jet Meridional Positions Between the Northern and Southern Hemispheres in CMIP6 Models - Li Tang; Riyu Lu; Zhongda Lin; Jian Lu; Ziming Chen (International Journal of Climatology, 2024)
This study investigates the inter‐model spread of climatological extratropical westerly jets in boreal winter, using the historical simulation of 52 Coupled Model Intercomparison Project phase 6 (CMIP6) models from 1851 to 2014. The results show that there is a substantial spread in the latitude of the upper‐tropospheric westerly jet across models, characterised by large inter‐model standard deviations to both the poleward and equatorward sides of the jet axis, although the multi‐model ensemble mean (MME) performs well in simulating meridional position of westerly jets. Furthermore, we detect the consistency of inter‐model jet position spread between the Northern and Southern Hemispheres, based on the inter‐model empirical orthogonal function (EOF) decomposition and correlation of regional‐averaged zonal winds. Specifically, the models that simulate the westerly jets poleward/equatorward relative to the MME position in one hemisphere also tend to simulate the jets poleward/equatorward in the other hemisphere. Accordingly, we define a global jet spread index to depict the concurrence of jet shift in the two hemispheres. The results of inter‐model regression analyses based on this index indicate that the models positioning the jets poleward than the MME tend to simulate a wider Hadley Cell, a poleward‐shifted Ferrel Cell in the Southern Hemisphere, enhanced precipitation in the subtropics and suppressed precipitation in the tropics, and warmer sea surface temperatures in the subtropics and mid‐latitudes. The present results suggest that improving the simulation of jet positions in climate models requires a comprehensive consideration of thermal states in the tropics and subtropics/mid latitudes.

Experimental and theoretical study on the burning and pulsation behaviors of hydrogen-containing and hydrocarbon jet flames - Ziming Lin; Kun Zhao; Situo Li; Zhenhua Tang (Process Safety and Environmental Protection, 2024)

Targeted quantitative metabolomic and flavor objective quantification technique reveal the impact mechanism of shaking on black tea quality and non-volatile metabolites - Jinjin Wang; Lichi Qu; Ziming Yu; Yongwen Jiang; Chengfa Yu; Xizhe Zhu; Qingju Lin; Linchi Niu; Yaya Yu; Qing Lin; Yan Shang; Haibo Yuan; et al. (Food Chemistry, 2024)

Self-template synthesis of PBA/MOF hollow nanocubes for aqueous battery - Yecan Pi; Hao Lin; Zhenyang Meng; Ziming Qiu; Yichun Su; Xinxin Hang; Huan Pang (Chemical Engineering Journal, 2024)

Influence of tangential hydrodynamic force and inclination angle calculation on the dynamic responses analysis of mooring line based on lumped mass method - Ziming Wang; Dongsheng Qiao; Qingshuai Wu; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean & Coastal Management, 2024)

On the modification of plant proteins: Traditional methods and the Hofmeister effect - Ziming Wang; Tiantong Lan; Jing Jiang; Tingyu Song; Jingsheng Liu; Hao Zhang; Ke Lin (Food Chemistry, 2024)

Monitoring system framework design for floating wind turbine using the deep learning technology and tower response identification considering sensor optimization - Ziming Wang; Dongsheng Qiao; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean Engineering, 2024)

Abscisic acid promotes selenium absorption, metabolism and toxicity via stress-related phytohormones regulation in Cyphomandra betacea Sendt. (Solanum betaceum Cav.) - Xun Wang; Wen Lu; Ziming Zhao; Wenhui Hao; Ruimin Du; Zhiyu Li; Zhihui Wang; Xiulan Lv; Jin Wang; Dong Liang; Hui Xia; Yi Tang; et al. (Journal of Hazardous Materials, 2024)

Cover Crops Control Weed and Improve Soil Qualities in Citrus Orchard - Hang Li; Xun Wang; Yuan Li; Yuhui Hou; Ziming Zhao; Lin Meng; Ji Liu; Jun Wang; Bo Xiong; Zhihui Wang (Journal of Soil Science and Plant Nutrition, 2023)

Facile preparation of nitrogen-doped microporous carbon from potassium citrate/urea for effective CH4 separation and uptake - Li Zhang; Yonggang Dong; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Yongyong Shi; Yutao Lv; Cuiwei Zhang; Hongyan Pan; Qian Lin (Fuel, 2023)

Electronic regulation and hydrophobicity improvement of the palladium active site by ionic liquid to achieve high selectivity direct synthesis of hydrogen peroxide - Lang Wu; Hong Qin; Songhua Zhou; Ziming Luo; Yang Xiao; Huan You; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

Macroalgae culture–induced carbon sink in a large cultivation area of China - Yingying Wang; Weifeng Yang; Yihua Cai; Ziming Fang; Xiufeng Zhao; Qinghua Zhang; Hao Yuan; Na Lin; Chenyi Zou; Minfang Zheng (Environmental Science and Pollution Research, 2023)

Self-assembled synthesis of Pd/SPEn from polyelectrolyte membranes for efficient direct synthesis of H2O2 via inhibiting the dissociation of O − O bond - Entong Ye; Zheng Chen; Yongyong Shi; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Quansheng Wu; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

Controlling Diels-Alder reactions in catalytic pyrolysis of sawdust and polypropylene by coupling CO2 atmosphere and Fe-modified zeolite for enhanced light aromatics production - Yao He; Junjie Chen; Ziming Mo; Changsong Hu; Detao Li; Jianhua Tu; Chen Lin; Yi Wang; Dongxia Liu; Tiejun Wang (Journal of Hazardous Materials, 2023)

Influence of circulation types on temporal and spatial variations of ozone in Beijing - Xiaowan Zhu; Jin Wu; Guiqian Tang; Lin Qiao; Tingting Han; Xiaomei Yin; Xiangxue Liu; Ziming Li; Yajun Xiong; Di He; Zhiqiang Ma (Journal of Environmental Sciences, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Differential Effects of Paclobutrazol on the Bulblet Growth of Oriental Lily Cultured In Vitro: Growth Behavior, Carbohydrate Metabolism, and Antioxidant Capacity - Yun Wu; MinYi Sun; JiaPing Zhang; Lin Zhang; ZiMing Ren; RuiHan Min; XiuYun Wang; YiPing Xia (Journal of Plant Growth Regulation, 2019)

Vertebrate Paralogous CRMPs in Nervous System: Evolutionary, Structural, and Functional Interplay - Yanyan Tang; Ziming Ye; Yunfei Wei; Cuiting Lin; Yongbo Wang; Chao Qin (Journal of Molecular Neuroscience, 2015)

Effects of extracellular calcium on viability and osteogenic differentiation of bone marrow stromal cells in vitro - Shaowen Cheng; Wei Wang; Zhongqin Lin; Ping Zhou; Xiaolei Zhang; Wei Zhang; Qingyu Chen; Dongquan Kou; Xiaozhou Ying; Yue Shen; Xiaojie Cheng; Ziming Yu; et al. (Human Cell, 2013)